The Impact of Neighborhoods on Intimate Partner Violence and Victimization - Pichevsky, Gillian M. (2012)
Research on intimate partner violence (IPV) and victimization is widespread across disciplines. To date, the majority of research underscores the importance of individual-level factors to explain IPV, thereby neglecting the significance of macro-level elements. Nevertheless, research suggests that the characteristics of the neighborhood where an individual lives are important for fully understanding IPV. This review focuses on the effects of neighborhoods and macro-level context on violence between intimate partners, specifically identifying empirical studies that have examined contextual predictors of IPV utilizing the major tenets of social disorganization theory. The authors note consistencies and differences across research results and describe study features that may influence the patterns of these findings. Finally, the authors provide both theoretical and methodological recommendations for future research